[OP.3B.01] THE ROLE OF INFLAMMATION IN THE ARTERIAL AGING AND ITS EFFECTS ON THE STRUCTURE OF THE AORTIC WALL, HEART FUNCTION AND METABOLISM. (September 2016) - Lambert, D.; Marie, P.-Y.; Lacolley, P.; Benetos, A.; Joly, L.
Abstract : Objective: Aging led to the development of a proinflammatory phenotype and organ dysfunction. In situations of metabolic syndrome, it is associated with an increase in arterial stiffness and blood pressure. The main objective of this project is to establish a link between inflammation and arterial aging in a situation of metabolic syndrome in arterial and heart levels. Design and method: The animal model chosen was a murine model developing metabolic syndrome. Mice received during a year, a high fat diet or a control diet. Systolic blood pressure and heart rate measurements were performed and the determination of metabolic parameters was performed. The Visualsonics®, a small animal echocardiography system, was used to study cardiac function and left ventricular dimensions. MicroPET (positron emission tomography) experiments were done in parallel for studying the metabolism. Finally the MRI (Magnetic resonance imaging) technique was used to locate the interscapular brown fat and determine the water ratio on fat for each animal. Results: Following a high fat diet, mice exhibit many of the characteristics of metabolic syndrome (hypertension, hypercholesterolemia, hyperglycemia, obesity). The echocardiographic results show an increase of left ventricular weight and an increase of the inter ventricular septum at 12 month of high fat diet. MRI allowed us to highlight a decrease in water to fat ratio in high fat diet mice expressing increased fat levels. Finally, we observed a hypo-glucose metabolism in brown fat and white fat by PET. Conclusions: An high fat diet leads to heart morphological changes and changes in the metabolism of fat and brown fat in particular. The UCP-1 protein might be involved and thus promote obesity and long-term storage. The link with the biological parameters still due.